Augmentation of drought stress tolerance of two wheat cultivars through exogenous spraying of silicon - Dawood, Mona Fathi Abd elmowla (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Two wheat cultivars cv. Sohag 3 (durum wheat) and cv. Seds 12 (bread wheat) were tested to assess their physiological behavior under different water regimes (100%, 70%, 50% and 30% FC) and their responsiveness to foliar application of 8mM silicon. The data clearly indicated the hypersensitivity of cv. Sohag 3 to water deficit as compared to cv. Seds 12 where dramatic reduction of shoots, roots, spikes and grains dry weight. Cv. Sohag 3 reduced total proteins and great accumulated of soluble proteins at the expense of insoluble one as well as reduction of soluble, insoluble and total carbohydrates. On the other hand, cv. Seds 12 maintained the insoluble proteins and enhanced of the soluble one as well as its ability to boost soluble, insoluble and total carbohydrates. In addition, water stress stimulated high oxidative damage in terms of overproduction of hydrogen peroxide, lipid peroxidation, electrolyte leakage and lipoxygenase enzyme of cv. Sohag 3 compared to oxidative damage limiting capacity of cv. Seds 12. Silicon application greatly augmented the water scarcity and exhibited better growth under harsh conditions due to the up- regulation of C and N- metabolism of the studied cultivars and reduced membrane damage as indicated by reducing H2O2, MDA, electrolyte leakage and lipoxygenase. All of these criteria answered on the stimulatory effect of silicon on yield attributes (spikes and grains) of the